Exploring the adoption of cutting-edge management practices by school principals - Hareb Almheiri, Abdulla Sultan; Abuhassna, Hassan (Institute of Advanced Engineering and Science, 2024)
This study examines the application of contemporary leadership trends by public school principals in the United Arab Emirates (UAE), with an emphasis on the professional standards governing school leadership. Utilizing a quantitative methodology, the study surveyed 113 principals from 641 schools. The validity of a 30-item questionnaire was rigorously evaluated to ensure that it aligned with the research objectives. This study’s findings reveal that school principals in UAE public schools implement contemporary leadership trends at a notable rate, as indicated by a substantial mean score of 4.24. Strategic management emerges as the primary focus among these trends. In addition, the research reveals statistically significant (0.05) gender and experience differences in participant responses regarding the actual adoption of modern leadership trends by government school principals. In contrast, there were no statistically significant differences (0.05) between participant responses regarding the incorporation of leadership trends by public school principals based on their academic credentials. This study highlights the importance of continuing training programs designed to keep school administrators abreast of the most recent leadership developments.